2009
DOI: 10.1128/jvi.02162-08
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Inhibiting Cap Addition and Cap Methylation on Polyadenylation during Vesicular Stomatitis Virus mRNA Synthesis

Abstract: The multifunctional large (L) polymerase protein of vesicular stomatitis virus (VSV) contains enzymatic activities essential for RNA synthesis, including mRNA cap addition and polyadenylation. We previously mapped amino acid residues G1154, T1157, H1227, and R1228, present within conserved region V (CRV) of L, as essential for mRNA cap addition. Here we show that alanine substitutions to these residues also affect 3-end formation. Specifically, the cap-defective polymerases produced truncated transcripts that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 44 publications
(54 reference statements)
3
41
0
Order By: Relevance
“…An rVSV containing a 132-nucleotide (nt) gene inserted at the leader-N gene junction (32) was used as the source of the 10-, 51-, and 110-nt RNAs containing the conserved elements of a VSV mRNA. The N-RNA template was purified from this virus and resuspended in 10 mM Tris-HCl (pH 7.4), 100 mM NaCl, and 1 mM EDTA as described previously (18). RNA was synthesized from 10 g of this template by using 3 g of the cap-defective (H1227A) rL mutant as described previously (18,19).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An rVSV containing a 132-nucleotide (nt) gene inserted at the leader-N gene junction (32) was used as the source of the 10-, 51-, and 110-nt RNAs containing the conserved elements of a VSV mRNA. The N-RNA template was purified from this virus and resuspended in 10 mM Tris-HCl (pH 7.4), 100 mM NaCl, and 1 mM EDTA as described previously (18). RNA was synthesized from 10 g of this template by using 3 g of the cap-defective (H1227A) rL mutant as described previously (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…The N-RNA template was purified from this virus and resuspended in 10 mM Tris-HCl (pH 7.4), 100 mM NaCl, and 1 mM EDTA as described previously (18). RNA was synthesized from 10 g of this template by using 3 g of the cap-defective (H1227A) rL mutant as described previously (18,19). To eliminate 5Ј-triphosphorylated RNA transcripts derived from the leader and N genes, we used oligonucleotides designed to anneal to nt 2 to 17 and 66 to 81 of the VSV antigenome and cleaved the resulting RNA-DNA hybrids with RNase H. Briefly, DNA primers were annealed at a 3:1 molar excess of the RNA transcripts and digested with 10 U of RNase H (Takara) for 30 min at 37°C in 60-l reaction mixtures, followed by digestion with 1 U of RQ1 DNase (Promega) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that rVSV-K1651A, a mutation in MTase active site and completely defective in G-N-7 and 2'-O methylation, synthesized excessively long poly(A) tails, similar to those produced by wild-type L in the presence of SAH [15]. Similarly, the substitution D1762E at the MTase active site, which inhibits both G-N-7 and 2'-O methylation, produces large polyadenylate in the presence or absence of SAH [97].…”
Section: The Effects Of 5' Mrna Cap Addition and Cap Methylation On 3mentioning
confidence: 99%
“…Cap formation is essential for mRNA stability, efficient translation, and gene expression [9][10][11]. It is now firmly established that mRNA capping and methylation in NNS RNA viruses evolves in a mechanism distinct to their hosts [12][13][14][15][16][17][18][19]. Thus, mRNA cap formation is an attractive antiviral target for NNS RNA viruses.…”
Section: Introductionmentioning
confidence: 99%